Pharmacological management of orofacial pain – a clinician's guide. (17th August 2020) - Clark, M.V.; Donnell, C.C.; Durham, J.; Balasubramaniam, R.
Abstract: Managing orofacial pain can be a daunting prospect for the dentally qualified clinician. This article aims to alleviate some of these concerns by providing guidance when pharmacological intervention may be recommended, alongside their dosing regimens and contraindications. The medications discussed include amitriptyline, nortriptyline, gabapentin, pregabalin, duloxetine, carbamazepine, oxcarbazepine, clonazepam, capsaicin, baclofen, lamotrigine, alpha‐lipoic acid, lidocaine hydrochloride and benzydamine hydrochloride. Management of orofacial pain is complex and, hence, often requires the input of specialists in secondary care. While the scope of this guide is aimed chiefly at pharmacological management by secondary care dental prescribers, a holistic approach encompassing all biopsychosocial factors is encouraged. The main take home points have been summarised in a table, aimed for use as a 'quick reference guide' during clinic sessions. Other contemporaneous prescribing guides and guidelines should always be used in conjunction with this article as licensing and dosing regimens of medications can be different around the world.